1983
DOI: 10.1099/0022-1317-64-12-2669
|View full text |Cite
|
Sign up to set email alerts
|

Localization by Immunogold Cytochemistry of Viral Antigen in Sections of Plant Cells Infected with Red Clover Mottle Virus

Abstract: SUMMARYRed clover mottle virus (RCMV) was detected by light and electron microscopy in sections of systemically infected pea leaf cells at successive stages of early infection using the combination of a sensitive immunocytochemical method with colloidal gold as a marker of antigen and a low temperature embedding procedure. Gold label was present in the cytoplasm at approximately the same time as the virus-induced membranous inclusions were established in the infected cells as judged by conventional electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…5). A similar distribution of virus particles was reported for another comovirus, red clover mottle virus, in pea leaf cells (Tomenius et al, 1983). No gold labelling was observed in sections of mock-inoculated protoplasts treated with anti-24K, -170K, -CPMV and Protein A-gold complex or in CPMV-infected protoplasts treated with preimmune serum and Protein A-gold complex.…”
supporting
confidence: 82%
“…5). A similar distribution of virus particles was reported for another comovirus, red clover mottle virus, in pea leaf cells (Tomenius et al, 1983). No gold labelling was observed in sections of mock-inoculated protoplasts treated with anti-24K, -170K, -CPMV and Protein A-gold complex or in CPMV-infected protoplasts treated with preimmune serum and Protein A-gold complex.…”
supporting
confidence: 82%
“…A similar problem was encountered by Brakke et al (1987) in studies of wheat leaf tissue infected with wheat streak mosaic virus. Tomenius et al (1983) reported gold labelling of the walls of xylem vessels in pea leaf tissue infected with red clover mottle virus, although it is not clear whether this labelling was regarded as virus-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the virus is plentiful in leaf tissue (Hemida & Murant, 1989a), virus particles were found by Murant et al (1975) only in membrane-walled tubules 45 nm in diameter which were usually associated with cell wall outgrowths. This paper describes an investigation of the location and distribution of PYFV particle antigen in leaf cells, using immunogold labelling of thin sections, an approach that has proved successful with several other plant viruses (Tomenius et al, 1983;Lin et al, 1987;Langenberg, 1986;Roenhorst et al, 1988). (Mutant & Goold, 1968), and of N. clevelandii containing isolate P-121.…”
Section: Introductionmentioning
confidence: 99%
“…In further studies (Tomenius et al 1984) using antibodies specific for the larger (40K) capsid protein of RCMV it was shown that label was generally distributed over the cytoplasm and among the membranes of the virusinduced inclusions. The capsid protein was detectable simultaneously with intact virus but could not be detected before the membraneous inclusion had developed.…”
Section: Applicationsmentioning
confidence: 98%
“…The low level of labelling is explained by the fact that only antigenic sites on the surface of the sections are accessible, the resin being impermeable to the antibodies. Tomenius et al (1983) used immunogold cytochemistry to localize red clover mottle virus (RCMV) antigen in infected pea leaf cells. Label was intense in the cytoplasm and among the membranes of the virus-induced membranous inclusions but not over the vesicles.…”
Section: Applicationsmentioning
confidence: 99%